A preparation process of highly dispersed antibacterial carbon black
Through a high dispersion antibacterial carbon black preparation process, the problem of poor dispersion and easy growth of mold in the paint is solved, high dispersion and strong antibacterial properties are achieved, and the stability and anti-mold of the paint are improved.
Patent Information
- Application Number
- CN202411786590.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-06
AI Technical Summary
Existing carbon blacks have poor dispersion and are prone to mold growth in the paint, resulting in problems such as graininess, fading and color differences after the paint is formed.
A high-dispersible antibacterial carbon black preparation process is adopted. By heating and ultrasonic dispersing the carbon black powder with the first mixed amino acid solution, then adding a mixed antibacterial agent solution and a surfactant, then adding chitosan solution and a second mixed amino acid solution, finally adding a mixed dispersant, and after heating, ultrasonication and drying treatment, a highly dispersible antibacterial carbon black is obtained.
It significantly improves the dispersion and antibacterial effect of carbon black, avoids the agglomeration of carbon black particles, and enhances the stability and anti-mold properties of the paint.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of carbon black, and in particular to a preparation process of highly dispersed antibacterial carbon black. Background Art
[0002] Carbon black is the product of incomplete combustion or cracking of hydrocarbons. Its main component is carbon. Using an electron microscope, one can observe a quasi-crystalline structure similar to graphite, which is similar to spherical colloidal particles or aggregates of particles fused together.
[0003] The application fields of carbon black include rubber industry, ink and coating industry, plastic industry, electronics industry, brake materials and other fields. Carbon black is added to the coating industry to play the role of coloring, reinforcement, UV protection and so on. However, the electrostatic effect between carbon black particles and the strong aggregation between carbon black particles will lead to adsorption problems between particles and unstable storage performance. Over time, carbon black will flocculate, resulting in granularity, discoloration and uneven color after the coating is formed. In addition, in a humid environment, the coating is prone to breeding mold and other harmful bacteria. At present, mildew inhibitors are added to the coating to inhibit the breeding of harmful bacteria such as mildew. Although the problem of harmful bacteria has been solved to a certain extent, the addition of mildew inhibitors will affect the performance of the coating, and the formed mildew-proof layer will become a new source of pollution. Therefore, in view of the above problems, it is necessary to develop a preparation process for highly dispersed antibacterial carbon black. Summary of the invention
[0004] The technical problem to be solved by the present invention is: in view of the deficiencies of the prior art, a preparation process of highly dispersed antibacterial carbon black is provided, by which highly dispersed antibacterial carbon black can be obtained.
[0005] In order to solve the above technical problems, the technical solution of the present invention is:
[0006] A preparation process of highly dispersible antibacterial carbon black, the preparation process comprising the following steps:
[0007] (1) taking a carbon black material, adding a first mixed amino acid solution to the carbon black powder obtained by grinding, heating, and ultrasonically dispersing the carbon black slurry for use;
[0008] (2) taking the carbon black slurry described in step (1), adding a mixed antibacterial agent solution and a surfactant, heating and ultrasonically treating the collected slurry for later use;
[0009] (3) Take the liquid prepared in step (2), add the chitosan solution, stir and mix, and then perform ultrasonic treatment to obtain a material for later use;
[0010] (4) Take the material described in step (3), add the second mixed amino acid solution, heat and ultrasonically disperse the material solution for later use;
[0011] (5) Take the liquid prepared in step (4), add a mixed dispersant, heat, grind, and dry to obtain a highly dispersed antibacterial carbon black product.
[0012] As an improved technical solution, the fineness of the carbon black powder in step (1) is less than 12 μm, and the carbon black powder is mixed with the first mixed amino acid solution in a mass volume ratio of 1:3-4; the first mixed amino acid solution is composed of aspartic acid, glutamic acid and purified water mixed in a mass volume ratio of 1-2:1-1.5:6-8.
[0013] As an improved technical solution, in step (1), the temperature is heated to 48-56° C., the power of the ultrasonic dispersion is 420-480 W, and the dispersion time is 20-30 min.
[0014] As an improved technical solution, the carbon black slurry in step (2) is mixed with the mixed antibacterial agent solution in a mass ratio of 1:0.2-0.5; the mixed antibacterial agent solution is a mixture of nano zinc, graphene oxide, 4,5-dichloro-N-octyl-4-isothiazoline-3-one and ethanol in a mass volume ratio of 1-3:0.5-1:1-2:10-15.
[0015] As an improved technical solution, in step (2), the temperature is heated to 60°C-75°C, the power of ultrasonic treatment is 400-500W, and the treatment time is 30-40min.
[0016] As an improved technical solution, the surfactant in step (2) is prepared by mixing sodium dodecylbenzene sulfonate and sodium lauroyl sarcosinate in a mass ratio of 1:1, and the amount of the surfactant added is 0.3-0.5% of the weight of the carbon black slurry.
[0017] As an improved technical solution, the amount of chitosan solution added in step (3) is 0.2-0.5% of the weight of the feed liquid; the concentration of the chitosan solution is 0.5-0.8wt%, and the chitosan solution is prepared from chitosan with a molecular weight of 10kD and 0.5-1wt% acetic acid; the power of the ultrasonic treatment is 300-360w, and the treatment time is 10-20min.
[0018] As an improved technical solution, the amount of the second mixed amino acid solution added in step (4) is 20-30% of the weight of the material; the second mixed amino acid solution is an aqueous solution of aspartic acid and threonine, wherein the aspartic acid and threonine are mixed with purified water in a mass volume ratio of 1-2:1-1.5:5-8.
[0019] As an improved technical solution, in step (4), the temperature is heated to 45-55°C, the power of ultrasonic dispersion treatment is 480-560W, and the dispersion time is 20-30min.
[0020] As an improved technical solution, in step (5), the feed liquid and the mixed dispersant are mixed in a mass ratio of 1:0.2-0.5; the mixed dispersant includes polyurethane dispersant HT-163 and polyurethane dispersant-F440, and the polyurethane dispersant HT-163 and polyurethane dispersant-F440 are mixed in a mass ratio of 1-2:1; the heating temperature is 90-105°C, and the grinding time is 20-30min.
[0021] After adopting the above technical solution, the beneficial effects of the present invention are:
[0022] The present invention grinds carbon black and then adds the first mixed amino acid solution, heats, ultrasonically disperses, and dries to obtain a modified carbon black material. A mixed antibacterial agent solution and a surfactant are then added, heated, and ultrasonically treated. A chitosan solution is then added to the obtained liquid, and the liquid is ultrasonically treated, concentrated, and dried to obtain carbon black with antibacterial properties. Then, a second mixed amino acid solution is added, and after heating and ultrasonic dispersion treatment, the carbon black is further modified. A mixed dispersant is then added, and the mixture is heated, ground, and dried to obtain highly dispersible antibacterial carbon black. The above process design is reasonable. By modifying the surface of the carbon black and wrapping the mixed antibacterial liquid adsorption layer, the chitosan solution adsorption layer, and the mixed dispersant adsorption layer, agglomeration between carbon black particles is avoided, and the dispersibility and mildew-proof effect of the carbon black are greatly improved. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention. Example 1
[0024] A preparation process of highly dispersible antibacterial carbon black comprises the following steps:
[0025] (1) Take a carbon black material, grind it to obtain 200 mg of carbon black powder with a fineness of 10 μm, add 600 ml of the first mixed amino acid solution (aspartic acid, glutamic acid and purified water are mixed in a mass volume ratio of 1:1:6, where the unit corresponding to w / v is mg / ml) in a mass volume ratio of 1:3, heat to 48°C, and ultrasonically disperse at a power of 420 W for 20 minutes to obtain 800 mg of carbon black slurry for use;
[0026] (2) Take 800 mg of the carbon black slurry in step (1), add 160 mg of a mixed antibacterial agent solution (nano zinc, graphene oxide, 4,5-dichloro-N-octyl-4-isothiazoline-3-one and ethanol mixed in a mass volume ratio of 1:0.5:1:10, where the unit corresponding to w / v is mg / ml) in a mass ratio of 1:0.2, then add 2.4 mg of a surfactant (sodium dodecylbenzene sulfonate and sodium lauroyl sarcosinate mixed in a mass ratio of 1:1) at a weight ratio of 0.3% of the weight of the carbon black slurry, heat to 60°C, ultrasonically treat at a power of 400 W for 30 min, and collect 962.4 mg of the slurry for use;
[0027] (3) Take 962.4 mg of the liquid in step (2), add 1.9 mg of a 0.5 wt% chitosan solution (the chitosan solution is prepared by mixing chitosan with a molecular weight of 10 kD and 0.5 wt% acetic acid) with a weight of 0.2% of the liquid, stir and mix, and then ultrasonically treat at a power of 300 W for 10 min to obtain 964.3 mg of material for use;
[0028] (4) Take 964.3 mg of the material in step (3), add 192.9 mg of the second mixed amino acid solution (mixed with aspartic acid and threonine and purified water in a mass volume ratio of 1:1:5) with a weight ratio of 20% of the material weight, heat to 45°C, and ultrasonically disperse at a power of 480 W for 20 min to obtain 1157.2 mg of the liquid for use;
[0029] (5) Take 1157.2 mg of the liquid in step (4), add a mixed dispersant (polyurethane dispersant HT-163 and polyurethane dispersant-F440 mixed in a mass ratio of 1:1) in a mass ratio of 1:0.2, heat to 90°C, grind for 20 minutes, and dry to obtain a highly dispersed antibacterial carbon black product. Example 2
[0030] A preparation process of highly dispersible antibacterial carbon black comprises the following steps:
[0031] (1) Take a carbon black material, grind it to obtain 200g of carbon black powder with a fineness of 8μm, add 640ml of the first mixed amino acid solution (aspartic acid, glutamic acid and purified water are mixed in a mass volume ratio of 1.2:1:6.5) at a mass volume ratio of 1:3.2, heat to 50°C, ultrasonically disperse at a power of 435W for 22min, and dry to obtain 840mg of carbon black slurry for use;
[0032] (2) Take 840 mg of the carbon black slurry in step (1), add 252 mg of a mixed antibacterial agent solution (nano zinc, graphene oxide, 4,5-dichloro-N-octyl-4-isothiazoline-3-one and ethanol mixed in a mass volume ratio of 1.5:0.8:1.2:11) in a mass ratio of 1:0.3, and then add 2.94 mg of a surfactant (sodium dodecylbenzene sulfonate and sodium lauroyl sarcosinate mixed in a mass ratio of 1:1) at a weight ratio of 0.35% of the weight of the carbon black slurry, heat to 65°C, and ultrasonically treat at a power of 420W for 32 minutes. Collect 1094.94 mg of the slurry for use;
[0033] (3) Take 1094.94 mg of the liquid in step (2), add 3.28 mg of chitosan solution (the chitosan solution is prepared by chitosan with a molecular weight of 10 kD and 0.8 wt% acetic acid) with a concentration of 0.6 wt% and a weight of 0.3% of the liquid, stir and mix, and then ultrasonically treat at a power of 315 W for 12 min to obtain 1098.2 mg of material for use;
[0034] (4) Take 1098.2 mg of the material in step (3), add 252.6 mg of the second mixed amino acid solution (mixed with aspartic acid and threonine and purified water in a mass volume ratio of 1.2:1.3:6) with a weight ratio of 23% of the material weight, heat to 48°C, and ultrasonically disperse at a power of 500 W for 22 min to obtain 1350.8 mg of the liquid for use;
[0035] (5) Take 1350.8 mg of the liquid in step (4), add a mixed dispersant (polyurethane dispersant HT-163 and polyurethane dispersant-F440 mixed in a mass ratio of 1.2:1) in a mass ratio of 1:0.3, heat to 95°C, grind for 23 minutes, and dry to obtain a highly dispersed antibacterial carbon black product. Example 3
[0036] A preparation process of highly dispersible antibacterial carbon black comprises the following steps:
[0037] (1) Take a carbon black material, grind it to obtain 200g of carbon black powder with a fineness of 5μm, add 700ml of the first mixed amino acid solution (aspartic acid, glutamic acid and purified water are mixed in a mass volume ratio of 1.5:1.3:7) at a mass volume ratio of 1:3.5, heat to 52°C, ultrasonically disperse at a power of 450W for 25min, and dry to obtain 900mg of carbon black slurry for standby use;
[0038] (2) Take 900 mg of the carbon black slurry in step (1), add 360 mg of a mixed antibacterial agent solution (nano zinc, graphene oxide, 4,5-dichloro-N-octyl-4-isothiazoline-3-one and ethanol mixed in a mass volume ratio of 2:0.8:1.5:13) in a mass ratio of 1:0.4, then add 3.6 mg of a surfactant (sodium dodecylbenzene sulfonate and sodium lauroyl sarcosinate mixed in a mass ratio of 1:1) at a weight ratio of 0.4% of the weight of the carbon black slurry, heat to 70°C, and ultrasonically treat at a power of 450 W for 35 min. Collect 1263.6 mg of the slurry for use;
[0039] (3) Take 1263.6 mg of the liquid in step (2), add 5.1 mg of chitosan solution (chitosan solution is chitosan with a molecular weight of 10 kD and 0.8 wt% acetic acid) with a concentration of 0.4% by weight of the liquid, stir and mix, and then ultrasonically treat at a power of 330 W for 15 min to obtain 1268.7 mg of material for use;
[0040] (4) Take 1268.7 mg of the material in step (3), add 317.2 mg of the second mixed amino acid solution (mixed with aspartic acid and threonine and purified water in a mass volume ratio of 1.5:1.3:7) with a weight ratio of 25% of the material weight, heat to 50°C, and ultrasonically disperse at a power of 520 W for 25 min to obtain 1585.9 mg of the liquid for use;
[0041] (5) Take 1585.9 mg of the liquid in step (4), add a mixed dispersant (polyurethane dispersant HT-163 and polyurethane dispersant-F440 mixed in a mass ratio of 1.5:1) in a mass ratio of 1:0.4, heat to 98°C, grind for 25 minutes, and dry to obtain a highly dispersed antibacterial carbon black product. Example 4
[0042] A preparation process of highly dispersible antibacterial carbon black comprises the following steps:
[0043] (1) Take a carbon black material, grind it to obtain 200g of carbon black powder with a fineness of 5μm, add 760ml of the first mixed amino acid solution (aspartic acid, glutamic acid and purified water are mixed in a mass volume ratio of 1.8:1.5:7.5) at a mass volume ratio of 1:3.8, heat to 54°C, and ultrasonically disperse at a power of 465W for 28min to obtain 960mg of carbon black slurry for use;
[0044] (2) Take 960 mg of the carbon black slurry in step (1), add 384 mg of a mixed antibacterial agent solution (nano zinc, graphene oxide, 4,5-dichloro-N-octyl-4-isothiazoline-3-one and ethanol mixed in a mass volume ratio of 2.5:1:1.8:15) in a mass ratio of 1:0.4, then add 4.32 mg of a surfactant (sodium dodecylbenzene sulfonate and sodium lauroyl sarcosinate mixed in a mass ratio of 1:1) at a weight ratio of 0.45% of the weight of the carbon black slurry, heat to 72°C, ultrasonically treat at a power of 480 W for 38 min, and collect 1348.3 mg of the slurry for use;
[0045] (3) Take 1348.3 mg of the liquid in step (2), add 5.4 mg of chitosan solution (chitosan solution is chitosan with a molecular weight of 10 kD and 1 wt% acetic acid) with a concentration of 0.6 wt% (0.4% by weight of the liquid), stir and mix, and then ultrasonically treat at a power of 345 W for 18 min to obtain 1353.7 mg of material for use;
[0046] (4) Take 1353.7 mg of the material in step (3), add 379 mg of the second mixed amino acid solution (mixed with aspartic acid and threonine and purified water in a mass volume ratio of 1.8:1.3:8) with a weight ratio of 28% of the material weight, heat to 52°C, and ultrasonically disperse at a power of 540 W for 28 min to obtain 1732.7 mg of the liquid for use;
[0047] (5) Take 1732.7 mg of the liquid in step (4), add a mixed dispersant (polyurethane dispersant HT-163 and polyurethane dispersant-F440 mixed in a mass ratio of 1.8:1) in a mass ratio of 1:0.4, heat to 102°C, grind for 28 minutes, and dry to obtain a highly dispersed antibacterial carbon black product. Example 5
[0048] A preparation process of highly dispersible antibacterial carbon black comprises the following steps:
[0049] (1) Take a carbon black material, grind it to obtain 200g of carbon black powder with a fineness of 5μm, add 800ml of the first mixed amino acid solution (aspartic acid, glutamic acid and purified water are mixed in a mass volume ratio of 2:1.5:8) at a mass volume ratio of 1:4, heat to 55°C, and ultrasonically disperse at a power of 480W for 30min to obtain 1000mg of carbon black slurry for use;
[0050] (2) Take 1000 mg of the carbon black slurry in step (1), add 500 mg of a mixed antibacterial agent solution (nano zinc, graphene oxide, 4,5-dichloro-N-octyl-4-isothiazoline-3-one and ethanol mixed in a mass volume ratio of 3:1:2:15) in a mass ratio of 1:0.5, then add 5 mg of a surfactant (sodium dodecylbenzene sulfonate and sodium lauroyl sarcosinate mixed in a mass ratio of 1:1) at a weight ratio of 0.5% of the weight of the carbon black slurry, heat to 75°C, ultrasonically treat at a power of 500 W for 40 min, and collect 1505 mg of the slurry for use;
[0051] (3) Take 1505 mg of the liquid in step (2), add 7.5 mg of a 0.8 wt% chitosan solution (the chitosan solution is prepared by chitosan with a molecular weight of 10 kD and 1 wt% acetic acid) with a weight of 0.5% of the liquid, stir and mix, and then ultrasonically treat at a power of 360 W for 20 min to obtain 1512.5 mg of the material for use;
[0052] (4) Take 1512.5 mg of the material in step (3), add 453.8 mg of the second mixed amino acid solution (mixed with aspartic acid and threonine and purified water in a mass volume ratio of 2:1.5:8) with a weight ratio of 30% of the material weight, heat to 55°C, and ultrasonically disperse at a power of 560 W for 30 min to obtain 1966.3 mg of the feed solution for use;
[0053] (5) Take 1966.3 mg of the liquid in step (4), add a mixed dispersant (polyurethane dispersant HT-163 and polyurethane dispersant-F440 mixed in a mass ratio of 2:1) in a mass ratio of 1:0.5, heat to 105°C, grind for 30 minutes, and dry to obtain a highly dispersed antibacterial carbon black product.
[0054] In order to better prove that the carbon black obtained by the process method of the present invention has good dispersibility and antibacterial effect, 15 comparative examples are given with reference to Example 3, as shown in the following content for details;
[0055] Performance Testing
[0056] Investigation of dispersion effect:
[0057] The carbon black prepared in Examples 1-5 and Comparative Examples 1-15 was placed in water at room temperature for 60 days to observe the dispersion effect of the carbon black, as shown in Table 1.
[0058] Investigation of antibacterial properties:
[0059] The carbon black products prepared in Examples 1-5 and Comparative Examples 1-15 were tested for Escherichia coli, Staphylococcus aureus and Aspergillus niger. 0.5 g of the prepared carbon black products were respectively placed in sterile test tubes, and a test solution diluted to 0.0001% was added. After ultrasonic treatment for 5 minutes, an equal amount of bacterial solution with a concentration of 0.0008% was added and mixed thoroughly. The Escherichia coli and Staphylococcus aureus tests were placed in a 37±1°C culture medium for 24 hours, and the Aspergillus niger test was placed in a 30±1°C culture medium for 120 hours ("-" represents no colony growth, and "+" represents colony growth); see Table 1 for details.
[0060] Comparative Example 1
[0061] The difference from Example 3 is that nitric acid is used to treat the carbon black powder in step (1), and the remaining operations are the same.
[0062] Comparative Example 2
[0063] The difference from Example 3 is that the temperature in step (1) is 45° C., and the remaining operations are the same.
[0064] Comparative Example 3
[0065] The difference from Example 3 is that L-serine is used instead of aspartic acid in step (1), and the remaining operations are the same.
[0066] Comparative Example 4
[0067] The difference from Example 3 is that no surfactant is added in step (2), and the remaining operations are the same.
[0068] Comparative Example 5
[0069] The difference from Example 3 is that the mixed antibacterial agent solution in step (2) does not contain graphene oxide, and the remaining operations are the same.
[0070] Comparative Example 6
[0071] The difference from Example 3 is that the mixed antibacterial agent solution in step (2) does not contain 4,5-dichloro-N-octyl-4-isothiazoline-3-one, and the remaining operations are the same.
[0072] Comparative Example 7
[0073] The difference from Example 3 is that the surfactant in step (2) does not contain sodium lauroyl sarcosinate, and the remaining operations are the same.
[0074] Comparative Example 8
[0075] The difference from Example 3 is that the temperature in step (2) is heated to 55° C., and the remaining operations are the same.
[0076] Comparative Example 9
[0077] The difference from Example 3 is that step (3) is missing, and the remaining operations are the same.
[0078] Comparative Example 10
[0079] The difference from Example 3 is that tyrosine replaces aspartic acid in step (4), and the rest of the operations are the same.
[0080] Comparative Example 11
[0081] The difference from Example 3 is that the temperature in step (4) is heated to 40° C., and the remaining operations are the same.
[0082] Comparative Example 12
[0083] The difference from Example 3 is that the amount of chitosan solution added in step (3) is 1% of the weight of the feed solution, and the rest of the operations are the same.
[0084] Comparative Example 13
[0085] The difference from Example 3 is that the mixed dispersant in step (5) does not contain polyurethane dispersant-F440, and the rest of the operations are the same.
[0086] Comparative Example 14
[0087] The difference from Example 3 is that the temperature is heated to 85° C. in step (5), and the remaining operations are the same.
[0088] Comparative Example 15
[0089] The carbon black material was taken and ground to obtain carbon black powder with a fineness of 5 μm without any other treatment.
[0090]
[0091] It can be found from the data in Table 1 that the carbon black product prepared by the preparation process of the present invention has a significantly better dispersibility than that of Example 1, Example 2, Example 4, Example 5 and Comparative Examples 1 to 15. In addition, the antibacterial property of the carbon black product prepared by Example 3 is better than that of Comparative Example 1, Comparative Examples 4 to 9, and Comparative Example 15.
[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A process for preparing highly dispersible antibacterial carbon black, characterized in that: The preparation process comprises the following steps: (1) A carbon black material is taken, and a first mixed amino acid solution is added to the carbon black powder with a fineness of less than 12 μm obtained by grinding, and the mixture is heated to 48-56° C. and ultrasonically dispersed to obtain a carbon black slurry for use; wherein the carbon black powder and the first mixed amino acid solution are mixed in a mass volume ratio of 1:3-4; the first mixed amino acid solution is a mixture of aspartic acid, glutamic acid and purified water in a mass volume ratio of 1-2:1-1.5:6-8; the power of the ultrasonic dispersion is 420-480 W, and the dispersion time is 20-30 min; (2) Take the carbon black slurry described in step (1), add a mixed antibacterial agent solution and a surfactant, heat to 60°C-75°C, and collect the liquid after ultrasonic treatment for use; wherein the carbon black slurry and the mixed antibacterial agent solution are mixed in a mass ratio of 1:0.2-0.5; the mixed antibacterial agent solution is a mixture of nano zinc, graphene oxide, 4,5-dichloro-N-octyl-4-isothiazoline-3-one and ethanol in a mass volume ratio of 1-3:0.5-1:1-2:10-15; the power of the ultrasonic treatment is 400-500W, and the treatment time is 30-40min; the amount of the surfactant added is 0.3-0.5% of the weight of the carbon black slurry, and the surfactant is a mixture of sodium dodecylbenzene sulfonate and sodium lauroyl sarcosinate in a mass ratio of 1:1; (3) Take the liquid prepared in step (2), add the chitosan solution, stir and mix, and then perform ultrasonic treatment to obtain a material for later use; (4) Take the material described in step (3), add the second mixed amino acid solution, heat to 45-55° C., and ultrasonically disperse the material for later use; wherein the amount of the second mixed amino acid solution added is 20-30% of the weight of the material; the second mixed amino acid solution is an aqueous solution of aspartic acid and threonine, wherein the aspartic acid and threonine are mixed with purified water in a mass volume ratio of 1-2:1-1.5:5-8; the power of the ultrasonic dispersion treatment is 480-560 W, and the dispersion time is 20-30 min; (5) Take the slurry described in step (4), add a mixed dispersant, heat, grind and dry to obtain a highly dispersed antibacterial carbon black product; wherein the slurry and the mixed dispersant are mixed in a mass ratio of 1:0.2-0.5; the mixed dispersant includes a polyurethane dispersant HT-163 and a polyurethane dispersant-F440, and the polyurethane dispersant HT-163 and the polyurethane dispersant-F440 are mixed in a mass ratio of 1-2:1; the heating temperature is 90-105°C, and the grinding time is 20-30min.
2. The process for preparing a highly dispersible antibacterial carbon black according to claim 1, characterized in that: The amount of chitosan solution added in step (3) is 0.2-0.5% of the weight of the feed solution; the concentration of the chitosan solution is 0.5-0.8wt%, and the chitosan solution is prepared from chitosan with a molecular weight of 10kDa and 0.5-1wt% acetic acid; the power of the ultrasonic treatment is 300-360W, and the treatment time is 10-20min.
Citation Information
Patent Citations
Preparation method of high-dispersity carbon black
CN118440519A
High-dispersity carbon black and preparation method thereof
CN118772666A